Prevalence and Pattern of Impacted Wisdom Teeth among a Sample of Iraqi People, Part 1 - M. Hamozi, Sarmad; M. Mohsin, Noorulhuda (International Journal of Psychosocial Rehabilitation, 2020)
Background and objectives: There is no doubt the impacted teeth play a major role in the healthy state of the patients because most of them are associated with pain and odontogenic problems affecting both hard and soft tissues, and so this study will throw light on their pattern and their behavior to emphasize, facilitate, and ease the researchers who are concerned with impacted teeth and give knowledge and a complete picture to the oral surgeons to ease their access and manipulation and assist them to get a proper design operation with little or no complications. Materials and methods: Retrospective data of 2138 OPG of patients from Najaf city was reviewed and classified the pattern of third molar impaction according to Winter’s classification and analyzed by one-sample Kolmogorov-Smirnov test and Pearson chi-square test to compare data regarding age groups and gender. Results: The incidence of impaction represented 1/5 to 1/4 of the population; the rate of impaction was more common in patients with impactions in both jaws than in patients with just mandibular or maxillary impactions. There was no significant difference between the left and right sides of the jaws; the impaction occurred 1.5 times more in females than males, and there was a highly significant difference among age groups. Conclusion: There was a high prevalence rate of impaction in Iraqi people in Najaf city; the high incidence of impaction pattern in the maxilla was distoangular impaction followed by mesioangular and vertical, while in the mandible it was vertical impaction followed by mesioangular and distoangular.